Apolinário Porto Alegre e os partenonistas: lendo os letrados do século XIX - Menez, Alexsandro da Rosa (2017)
This dissertation consists of an analytical and methodological experimentation, focusing on a complexification of the relationship between Literature and History, in their various forms of temporal perception. In this sense, through the knowledge constituted in both disciplinary spheres, the objective was the historical reading of Apolinário Porto Alegre and the parthenonists, South Rio-Grandense literates of the 19th century through an approach that started from the various analysis undertaken by different scholars, both from historical and literary studies, covering the period from 1919 to 2015. For this reason, this work did not aim at a simple bibliographical review on the subject, since the need for a renewal in the field of Brazilian literary historiography was identified, based on the reflexive sophistication of elements such as regionalism and nationalism, as well as different forms of community self-perception related to the identification of the need to enter various layers and temporal spaces on the theme.